2017
DOI: 10.1080/19440049.2017.1322222
|View full text |Cite
|
Sign up to set email alerts
|

Migration of oligomers from PET: determination of diffusion coefficients and comparison of experimental versus modelled migration

Abstract: Polyethylene terephthalate (PET) is increasingly used as food-contact material in, for example, containers for beverage such as bottles for soft drinks, mineral water, juices and beer. Mass transport of substances present in packaging materials into the packed food and beverages is monitored to verify the food law compliance of the materials. PET is known to contain or give rise to migrants that are oligomers derived from the polymeric material. Until now their actual migration potential has been investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 25 publications
4
43
0
Order By: Relevance
“…Several scientists (Greifenstein et al, 2013;Sánchez-Martínez et al, 2013;Welle and Franz, 2011) confirmed contamination of PETE-packaged foodstuffs and soft drinks with leaching Sb. Hoppe et al (2017) confirmed the leachability of oligomers from PETE that, according to their findings, have originated from the polymeric material. Phthalate esters, used as plasticizers, where found by Keresztes et al (2013) to migrate from PETE containers into packaged water.…”
Section: Introductionsupporting
confidence: 68%
“…Several scientists (Greifenstein et al, 2013;Sánchez-Martínez et al, 2013;Welle and Franz, 2011) confirmed contamination of PETE-packaged foodstuffs and soft drinks with leaching Sb. Hoppe et al (2017) confirmed the leachability of oligomers from PETE that, according to their findings, have originated from the polymeric material. Phthalate esters, used as plasticizers, where found by Keresztes et al (2013) to migrate from PETE containers into packaged water.…”
Section: Introductionsupporting
confidence: 68%
“…From day 1, the volatiles PS oligomers 2,4,6,-triphenyl -1-hexene and 1,3,5-triphenyl cyclohexane were already being formed, while also styrene and α-methyl styrene were generated. It is worthy to notice that for many other polymers, such as in the case of polyethylene terephthalate (PET), the trimer has been described as the most abundant structure [30,31]. 2,4-DTBP was also identified.…”
Section: Release and Fate Of The Identified Chemical Compoundsmentioning
confidence: 99%
“…Among the most relevant PES are polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polytrimethylene terephthalate (PTT). PET is selected for food contact materials (FCMs) due to its impact resistance, strength, flexibility and resistance to high temperatures (Ting Wu et al, 2014 ; Hoppe, Fornari, de Voogt, & Franz, 2017 ). Since recently PBT is also used in FCM applications such as coffee capsules, oxygen-barrier films, kitchenware, microwaveable dishware ( Brenz et al, 2017 , Brenz et al, 2018 ), whereas the use of PTT still remains restricted to the textile and automotive industry ( Piccinini, Senaldi, & Alberto Lopes, 2014 ).…”
Section: Introductionmentioning
confidence: 99%